Microstructure and electrical and optical properties of ZnO based varistor ceramics with small-amount of MnOշ and Co3O4 as dopant - Adnin, Noorfauzana (2012)
Various stresses such as high electric fields, high temperature and aggressive ambient can inflict serious damages on machinery and other equipments and may degrade the performances of ZnO varistor devices. To develop a high performance of ZnO varistor ceramics, the influences of dopant are very crucial to be understood since dopants are responsible for the formation of varistor behavior. Therefore, small amount of MnO2 and Co3O4 as dopant is added to ZnO system respectively to improve the varistor properties. Although there were numerous studies on the effect of dopant on ZnO varistor, the exact roles of “small amount” dopant in ZnO varistor and how it can improve the nonlinear Current - Voltage (I-V) characteristics have not yet been clarified. In this study, the microstructure, electrical and optical properties of the ZnO - xMnO2 and ZnO - xCo3O4 systems have been investigated for small amount of x ranging from 0.011 - 0.026 mol % at various sintering temperatures from 1180 - 1300 ºC for the sintering time of 1 and 2 hours. XRD analysis shows that the main phase was ZnO with ZnMnO3, ZnMnO7 and Co3O4 as the secondary phases developed in the material systems. The maximum density have been achieved up to about 98% of theoretical density at 1300 ºC sintering temperature at 0.011 mol % doping level of Co3O4 and the relative density in general, has the value above 85%. The maximum grain size was found to be 14 μm at the highest sintering temperature which is at 1300 ºC at 0.021 mol % of Co3O4 doping level. It was also found that MnO2 is a grain enhancer and promotes the grain growth of the ZnO samples. SEM and EDAX results verify that Mn and Co ions are distributed in the grain interior as well as in the grain boundaries. The value of nonlinear coefficient α, is found to increase with the amount of MnO2 up to 0.016 mol% doping level, while slightly change with the amount for Co3O4 mol%. Also, the value of nonlinear coefficient increases with the increase of sintering temperature and time for all ZnO system. An optimum sintering temperature of 1300 oC at 2 hour sintering time for ZnO + 0.016% MnO2 gave the best electrical properties, with the non-linear coefficient value α, attaining a highest value of 9.11 in which represent fast response to transient voltage, Nthus give high protective function of ZnO varistor. The band gap energy Eg, decreases with the increase of Co3O4 and MnO2 doping level and also sintering temperature respectively. For both dopants, the maximum decrease in the band gap occur at 0.026 mol % doping level at 1300 ºC for 1 hour sintering time with the value of 2.65 and 2.46 respectively. It is found that, the introduction of “small amount” MnO2 and Co3O4 dopant influences the microstructure, electrical and optical properties of all ZnO systems. The electrical characteristics of all ZnO samples depend on their microstructure properties. For both dopant, the growth of interface states are responsible for the decrement of the energy band gap value.